THE EFFECT OF THE "KELAS IBU HAMIL" APPLICATION ON DELIVERY PREPAREDNESS IN PREGNANT WOMEN - Asirotul Marifah (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Good delivery preparedness significantly reduces maternal and infant complications. Pregnant mother's classes are crucial for enhancing this readiness, now available in flexible digital formats alongside traditional face-to-face sessions due to technological advancements. However, the systematic effectiveness of these digital classes requires further proof. This study aimed to evaluate the impact of the "Kelas Ibu Hamil" application on delivery preparedness. The research employed a quasi-experimental design with a control group. The study population comprised 40 pregnant women receiving Antenatal Care at Puskesmas Pembantu Tambak Agung, Puri, Mojokerto. Total sampling ensured all eligible women became respondents, with 20 assigned to an intervention group using the "Kelas Ibu Hamil" application and another 20 to a control group receiving routine education. Delivery preparedness was measured using a specific questionnaire. Data analysis utilized the Paired Sample T-Test. Results indicated a significant difference in pre-test and post-test scores across four weeks (p < 0.05). These findings confirm that the application effectively improves delivery preparedness by enabling mothers to learn independently, access materials anytime, and consult healthcare professionals directly.